AN EXAMINATION OF VOLUNTARY DISCLOSURE, INDEPENDENT BOARD, INDEPENDENT AUDIT COMMITTEE AND INSTITUTIONAL OWNERSHIP: FIRM SIZE AS A MODERATOR - Pangaribuan, Hisar (Jurnal Muara Ilmu Ekonomi dan Bisnis, 2018)
: This study examines the impact of the independent board, independent audit committee and institutional ownership on voluntary disclosure (by placing company size as a moderating variable) in Indonesia banking companies. Data collected from the annual report of banking companies listed on the Indonesia Stock Exchange throughout the year of study. Hypotheses developed to be tested with a variance based approach and the results were interpreted. The result has shown that the increase of independent board members and independent audit committee members tend to decrease the level of voluntary disclosure (although the impact is not significant). Independent board and independent audit committee performed this to reduce cost due to a high disclosure and to avoid the threat of high competition in banking companies. The other result has shown that institutional investors are considered more professional and powerful in supervising management to disclose more information to the public. The final section of the study's findings indicated that firm size cannot be as a moderating variable on the impact of the independent board, independent audit committee and institutional ownership toward voluntary disclosure. Studi ini meneliti dampak dewan independen, komite audit independen dan kepemilikan institusional terhadap pengungkapan sukarela (dengan menempatkan ukuran perusahaan sebagai variabel moderasi) di perusahaan perbankan Indonesia. Data dikumpulkan dari laporan tahunan perusahaan perbankan yang terdaftar di Bursa Efek Indonesia sepanjang tahun studi. Hipotesis dikembangkan untuk diuji dengan pendekatan berbasis varians dan hasilnya ditafsirkan. Hasilnya menunjukkan bahwa peningkatan anggota dewan independen dan anggota komite audit independen cenderung menurunkan tingkat pengungkapan sukarela (walaupun dampaknya tidak signifikan). Dewan independen dan komite audit independen melakukan ini untuk mengurangi biaya karena pengungkapan yang tinggi dan untuk menghindari ancaman persaingan yang tinggi di perusahaan perbankan. Hasil lain menunjukkan bahwa investor institusional dianggap lebih profesional dan kuat dalam mengawasi manajemen untuk mengungkapkan lebih banyak informasi kepada publik. Bagian terakhir dari temuan penelitian menunjukkan bahwa ukuran perusahaan tidak dapat sebagai variabel moderat pada dampak dewan independen, komite audit independen dan kepemilikan institusional terhadap pengungkapan sukarela. Kata Kunci : Pengungkapan Sukarela, Dewan Independen, Komite Audit Independen, Kepemilikan Institusional, Ukuran Perusahan